Fraud Triangle Sebagai Pendeteksi Kecurangan Laporan Keuangan - Wahyuni Wahyuni; Gideon Setyo Budiwitjaksono (Jurnal Akuntansi, 2017)
The  financial  statements  arestructured  representation  of  the  financialposition shows the financialperformance of an entity. On the other hand, the FinancialServices Authority in Indonesia gave the sanction to capital market players for cheatingFinancial  Statements.This  shows  that  the  financial  statement  fraud  cases  occurring  inIndonesia  are  part  of  the  failure  of  an  audit  conducted  by  the  Public  Accounting  Firm(KAP).This  study  aims  to  examine  the  influence  of  fraud  triangle  in  detectingfraudulent  financial  statements.  The  object  of  this  study  using  the  financial  statementsof  companies  listed  on  the  Indonesia  Stock  Exchange  in  the  2012-2014  time  period.This  study  uses  123  data  samples  are  taken  using  purposive  criteria.  The  data  wereanalyzed   using   multiple   linear   regressionanalysis.The   results   showed   thatrazionalization  significant  effect  on  the  financial  statements  fraud.  Meanwhile,  thefinancial  stability,  external  pressure,  financial  targets,  the  nature  of  the  industry,ineffective  monitoring  did  not  significantly  affect  the  financial  statements  fraud.  Thisstudy  contributes  to  the  regulators  to  adopt  measures  to  improve  the  quality  of  audits,especially in detecting fraud.